The generation of hierarchic structures via robust 3D topology optimisation. (August 2017) - Hofmeyer, Hèrm; Schevenels, Mattias; Boonstra, Sjonnie
Highlights: Hierarchic layout of structural elements is shown to be optimal from a structural point of view. For a floor design domain robust optimisation yields closed boarding on top of bridging joists. Robust optimisation, more than Heaviside alone, gives crisp black-and-white distributions. Crisp black-and-white distributions are indispensable for additive manufacturing, i.e. 3D printing. Abstract: Commonly used building structures often show a hierarchic layout of structural elements. It can be questioned whether such a layout originates from practical considerations, e.g. related to its construction, or that it is (relatively) optimal from a structural point of view. This paper investigates this question by using topology optimisation in an attempt to generate hierarchical structures. As an arbitrarily standard design case, the principle of a traditional timber floor that spans in one direction is used. The optimisation problem is first solved using classical sensitivity and density filtering. This leads indeed to solutions with a hierarchic layout, but they are practically unusable as the floor boarding is absent. A Heaviside projection is therefore considered next, but this does not solve the problem. Finally, a robust approach is followed, and this does result in a design similar to floor boarding supported by timber joists. The robust approach is then followed to study a floor with an opening, two floors that span in two directions, and an eight-level concrete building. It can be concluded that a hierarchic layout of structural elements likely originates from being optimal from a structural point of view. Also clear is that this conclusion cannot be obtained by means of standard topology optimisation based on sensitivity or density filtering (as often found in commercial finite element codes); robust 3D optimisation is required to obtain a usable, constructible (or in the future: 3D printable) structural design, with a crisp black-and-white density distribution.